Estimated budgets for separate-site swine production - Kevin C Dhuyvetter; Michael D Tokach; R D Jones (Kansas Agricultural Experiment Station Research Reports, 1995)
Budgets were developed to help Kansas swine producers analyze the economics of separate-site production. Return on investment (ROI) was estimated at 9.5%in each of the three production phases. Returns over total costs were very sensitive to transfer price between phases (weaned pig and feeder pig price) as well as production efficiencies and input costs.; Swine Day, Manhattan, KS, November 16, 1995
Keywords: Swine day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-140-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 746; Swine; Economics; Budgets; Separate-site production